2013
DOI: 10.1016/j.cellsig.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

RKIP regulates MAP kinase signaling in cells with defective B-Raf activity

Abstract: MAP kinase (MAPK) signaling results from activation of Raf kinases in response to external or internal stimuli. Here, we demonstrate that Raf Kinase Inhibitory Protein (RKIP) regulates the activation of MAPK when B-Raf signaling is defective. We used multiple models including mouse embryonic fibroblasts (MEFs) and primary keratinocytes from RKIP- or Raf-deficient mice as well as allografts in mice to investigate the mechanism. Loss of B-Raf protein or activity significantly reduces MAPK activation in these cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…As the mechanism for p-Erk increase, we observed the RKIP reduction (Figure 2 ). Although RKIP is well known inhibitor of Raf kinase, it can also block the MEK1/2 activation [ 32 ]. In fact, silica-induced p-Erk was not suppressed by MEK1/2 inhibitors (Figure 1E ).…”
Section: Discussionmentioning
confidence: 99%
“…As the mechanism for p-Erk increase, we observed the RKIP reduction (Figure 2 ). Although RKIP is well known inhibitor of Raf kinase, it can also block the MEK1/2 activation [ 32 ]. In fact, silica-induced p-Erk was not suppressed by MEK1/2 inhibitors (Figure 1E ).…”
Section: Discussionmentioning
confidence: 99%
“…Code S1. A text file with computer-readable model implementation written in BNGL References (49)(50)(51)(52)(53)(54)(55)(56)…”
Section: Computational Modelingmentioning
confidence: 99%
“…Subsequent studies confirmed the function of RKIP as RAF1 inhibitor [ 53 , 54 ]. It was found that RKIP, depending on the cellular background, not only inhibits RAF1 but also BRAF [ 55 , 56 , 57 ].…”
Section: Tumour Suppressor Functions Of Rkipmentioning
confidence: 99%